Short Communication: Biometric of freshwater crayfish (Cherax spp.) from Papua and West Papua, Indonesia - ABINAWANTO ABINAWANTO; HANI HAMIDAH; ANOM BOWOLAKSONO; RURY EPRILURAHMAN (Society for Indonesian Biodiversity, 2018)
Abinawanto, Hamidah H, Bowolaksono A, Eprilurahman R. 2018. Short Communication: Biometric of freshwater crayfish (Cherax spp.) from Papua and West Papua,, Indonesia. Biodiversitas 19: 489-495. Freshwater crayfish, Cherax spp. is a native crayfish species in Papua, Indonesia. Biometric information of this crayfish species in Indonesia is limited. Hence, this study aimed to provide these data. Specimens were collected from West Papua Province, i.e., from Uter Lake (Atinjo Subdistrict, Maybrat) and Seremuk River (Haha Village, Seremuk Subdistrict, South Sorong), respectively. Besides, the specimens were also collected from Papua Province in Baliem River at Pike Village, Hubukiak Subdistrict, and Wesaput Village, Wesaput Subdistrict, Jayawijaya. Data were analyzed using canonical discriminant function (CDF). The results showed that the longest carapace of Cherax spp. was 97.83 mm found in Baliem River at Pike Village. CDF analysis showed that there were three population groups of Cherax spp. from four locations. The first group originated from Uter Lake (Atinjo Subdistrict) and Seremuk River (Haha village). The second group was from Baliem River (Pike Village; Hubukiak Subdistrict, Jayawijaya and the third group from Baliem River (Wesaput Village; Wesaput Subdistrict)